A re-evaluation of taxonomy in Quercus section Lobatae subsection Racemiflorae (Fagaceae), resurrection of the name Q. pennivenia and description of a new taxon, Q. huicholensis - Mccauley, Ross A.; Oyama, Ken (Phytotaxa, 2020)
Changes to the taxonomy of Quercus section Lobatae subsection Racemiflorae occurring in western Mexico are here made to reflect new evidence regarding species relationships of two lineages occurring in the southern Sierra Madre Occidental. The name Q. pennivenia is resurrected to recognize plants previously included under the name Q. urbanii. A new taxon, Q. huicholensis, is described to represent a distinct lineage segregated from Q. conzattii. With these nomenclatural changes we recognize the subsection Racemiflorae to consist of six taxa and we provide a key for their determination.